How and when do attributions affect relationship satisfaction? Judgments of partner suitability and implicit theories of relationships - WEE, Justus Rui Hao (Institutional Knowledge at Singapore Management University, 2017)
Drawing on the traditional internal-external dichotomy embraced by attribution research in other non-relational domains, research on attributions in romantic relationships has largely focused on distinguishing between the impact of making partner (internal) and external attributions. Given that past research on relationship cognitions showed that people think in relationship specific ways (e.g., relational schemas; Baldwin, 1992), I propose the need for the inclusion for attributions that capture relationship-specific causes. With that in mind, the present research explored the incremental value of interpersonal attributions, which refer to the perception that a partner’s behaviors are caused by their love and care (or lack of) for the self and/or the relationship. To establish the importance of interpersonal attributions in relationship research, the aims of the present research are fourfold: 1) to develop a new measure of interpersonal attributions; 2) to demonstrate the unique predictive value of interpersonal attributions on relationship outcomes, beyond internal and external attributions; 3) to illuminate the process through which interpersonal attributions predict relationship satisfaction; and 4) to explore the boundary conditions of the effects of interpersonal attributions. Findings from three studies highlight the importance of moving beyond the dichotomy of internal-external attributions in relationship research. First, factor analyses of data from longitudinal (Study 1) and cross-sectional (Study 2) studies demonstrate that interpersonal attributions represent a discrete factor not captured by the internal-external distinction. Second, regression results showed that interpersonal attributions predict relationship satisfaction, over and above internal and external attributions. Taken together, these two findings provide evidence for the incremental value of interpersonal attribution. Next, with the aim of explicating the direct effects between attributions and relationship satisfaction, Study 3 tests a moderated mediation model. Study 3 showed that the effects of interpersonal attributions on relationship satisfaction were mediated by cognitive and affective responses [Perceived Relationship Quality Component Index (PRQC index); Fletcher, Simpson, & Thomas, 2000] as well as partner perceptions [Interpersonal Qualities Scale (IQS); Murray, Holmes, & Griffin, 2000]. Furthermore, these effects were not moderated by the belief that effort can cultivate a successful relationship (i.e., growth theory; Knee, 1998). Overall, the findings suggest that the inclusion of interpersonal attributions contribute meaningfully to the discourse on the impact of divergent attribution patterns for partner’s behaviors in close relationships.